Comprehensive analysis and multi-objective optimization of a power and hydrogen production system based on a combination of flash-binary geothermal and PEM electrolyzer. (1st October 2021) - Fan, Guangli; Yang, Boyuan; Guo, Peixi; Lin, Shuchao; Farkoush, Saeid Gholami; Afshar, Nima
Abstract: In this study, comprehensive energy, exergy, and economic modeling, and optimization of a flash-binary geothermal system, were carried out for power and hydrogen production. The binary system is a combination of a dual-pressure organic Rankine cycle and proton exchange membrane electrolyzer. For performance improvement of dual-pressure organic Rankine cycle, zeotropic mixtures were used as the working fluids. The multi-objective Genetic algorithm was employed to optimize the system performance. According to the obtained results, the highest rate of exergy destruction was obtained for the steam turbine with a value of 16.42 kW . For the base case simulation, the energy and exergy efficiencies of the proposed system were obtained by 16.66 % and 58.03 %, respectively; also, the generated power, overall exergy destruction, and hydrogen production capacity were calculated by 114.53 kW, 82.755 kW, and 0.306 kg · hr − 1, respectively. For the multi-objective optimization mode, the best performance was calculated for Pentane ( 0.467 )/Butane ( 0.533 ) with energy and exergy efficiencies and hydrogen production of 16.67 %, 58.14 %, and 0.37 kg · hr − 1 . Moreover, the optimized payback period and NPV were around 5.52 years and 402600 , respectively. Highlights: Proposal of a flash-binary geothermal system for power and hydrogen production. Using zeotropic mixtures for performance improvement of dual-pressure ORC. Analyzing economic aspects of the proposed system for probable investment. Energy and exergy efficiencies of 16.67 % and 58.14 % for the optimized mode. Optimized payback period and total profit of 5.52 years and 402800 .